Congenital muscular torticollis: an Orl’s perspective - Swapna, C. A.; Siva Kumar, E.; Karanam, Lavanya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Congenital muscular torticollis usually results from the shortening or excessive contraction of sternocleidomastoid muscle. Delay in diagnosis and appropriate early therapeutic evaluation can lead to permanent disability. We would like to report two rare cases with congenital muscular torticollis who underwent surgery followed by aggressive physiotherapy. We would like to emphasise the need of an early diagnosis and intervention which leads to best outcome. This can prevent progressive physical deformity. Surgeons should offer the patient with option of release and repair of sternocleidomastoid muscle as it gives excellent result in view of mobility and appearance for child.